2002
DOI: 10.1194/jlr.m200261-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

α-Tocopherol protects against diet induced atherosclerosis in New Zealand white rabbits

Abstract: In this study, we asked the question "does ␣ -tocopherol supplementation prevent an increase in total plasma cholesterol (TPC) concentration and reduce the deposition of cholesterol in arterial plaques of rabbits fed atherogenic diets?" Isocaloric diets containing 0.1% cholesterol to induce atherosclerosis were enriched in one of three fats: saturated fats (SAT), monounsaturated fats (MONO), or n-6 polyunsaturated fats (POLY). Half of each of the three diets were supplemented with 2,500 IU ␣ -tocopherol/kg-die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 100 publications
(112 reference statements)
1
26
0
4
Order By: Relevance
“…However, randomized clinical trials and epidemiologic studies addressing the preventive effects of vitamin E supplementation against cardiovascular disease related to atherosclerosis reported both positive and negative effects [32,33], raising the question whether vitamin E might conditionally exert its protective effects on cardiovascular disease. In addition, most of the previous animal studies focus on the preventive effect of vitamin E supplementation at early stages of atherosclerosis and reach the expected results [29,34,35]. Meydani et al [36] recently reported that the effect of vitamin E on atherosclerosis depends on the blood lipid levels, lesion degree and disease stages using the LDLR knockout mouse as an atherosclerosis model as well as duration and time point of vitamin supplementation.…”
Section: Introductionmentioning
confidence: 97%
“…However, randomized clinical trials and epidemiologic studies addressing the preventive effects of vitamin E supplementation against cardiovascular disease related to atherosclerosis reported both positive and negative effects [32,33], raising the question whether vitamin E might conditionally exert its protective effects on cardiovascular disease. In addition, most of the previous animal studies focus on the preventive effect of vitamin E supplementation at early stages of atherosclerosis and reach the expected results [29,34,35]. Meydani et al [36] recently reported that the effect of vitamin E on atherosclerosis depends on the blood lipid levels, lesion degree and disease stages using the LDLR knockout mouse as an atherosclerosis model as well as duration and time point of vitamin supplementation.…”
Section: Introductionmentioning
confidence: 97%
“…Organic layers were combined and evaporated under a stream of Ar at 37°C then redissolved in 1 ml of ethanol. Sample preparation was based on the method of Metcalfe et al (47) as used previously (48). The sample in ethanol was treated with 0.1 ml of 50% aqueous KOH, the tube was purged with Ar, and then heated to 60°C for 1 hour.…”
Section: Fa and Phospholipid Analysismentioning
confidence: 99%
“…Then triglycerides were eluted with 3-8-ml washes of CH 2 Cl 2 :diethyl ether:hexane (14:1:84). Quantitation was by gas chromatography-mass spectrometry after saponifi-cation to generate methylated fatty acids (55,56). The fatty acids were quantified to obtain the total fatty acid composition.…”
Section: Methodsmentioning
confidence: 99%